Differences in medical costs between TCM users and TCM nonusers in inpatients with thalassemia - Zhaoran Han; Hanlin Nie; Zhengwei Huang; Zegui Tuo; Sisi Chen; Yong Ma; Xuefeng Shi (BMC, 2023)
Abstract Background Thalassemia has brought serious health threats and economic burdens to patients worldwide. There is no sovereign remedy for thalassemia, both conventional and Traditional Medicine (TM) methods have certain effects on this disease. As typical of TM, Traditional Chinese Medicine (TCM) has been widely used in the treatment of thalassemia. Previous studies mainly focused on conventional treatments for thalassemia and patients' medical burden, but no research has examined the effects of TCM use on the economic burdens for thalassemia inpatients in mainland China. The main objective of this study is to compare the medical cost differences between TCM users and TCM nonusers, furtherly, we will discuss the role of TCM use in the treatment of thalassemia. Methods We employed the 2010-2016 Medicare claims database provided by the China Health Insurance Research Association (CHIRA). Chi-square and Mann-Whitney tests were used to analyze the differences between TCM users and TCM nonusers. Multiple regression analysis was performed using the ordinary least squares method to compare the TCM users' inpatient medical cost with TCM nonusers', and to further examine the correlation between TCM cost, conventional medication cost and nonpharmacy cost for TCM users. Results A total of 588 urban thalassemia inpatients were identified, including 222 TCM users and 366 TCM nonusers. The inpatient medical cost of TCM users was RMB10,048 (USD1,513), which was significantly higher than TCM nonusers (RMB1,816 (USD273)). Total inpatient cost for TCM users was 67.4% higher than those of TCM nonusers (P < 0.001). With confounding factors fixed, we found that the conventional medication cost and nonpharmacy cost were positively correlated with TCM cost. Conclusion Total hospitalization expenses for TCM users were higher than TCM nonusers. Both the conventional medication cost and nonpharmacy cost of TCM users were all higher than TCM nonusers. We infer TCM plays a complementary role, rather than an alternative, in the treatment of thalassemia due to the lack of cooperative treatment guidelines. It is recommended that a cooperative diagnosis and treatment guidelines should be generated to balance the use of TCM and conventional medicine for treating thalassemia, so as to reduce the economic burdens on patients.